Gender Differences in Smoking Among an Urban Emergency Department Sample - Carol B Cunradi; Juliet Lee; Anna Pagano; Raul Caetano; Harrison J Alter (SAGE Publishing, 2019)
Background: Urban emergency department (ED) patients have elevated smoking and substance use compared with the general population. We analyzed gender differences in smoking among an urban ED sample and assessed the contribution of substance use, demographic, and couple factors. Methods: We conducted a secondary analysis of data obtained from a cross-sectional, observational survey (N = 1037 participants) on drinking, drug use, and intimate partner violence (IPV). Gender-specific logistic regression models for current (past 30-day) smoking and multinomial regression models for smoking intensity (light: ⩽5 cigarettes per day [CPD]; moderate: 6 to 10 CPD; heavier: >10 CPD) were estimated. Results: Smoking prevalence was higher among men than women (35.5% vs 18.9%; P < .001). Substance use (frequency of intoxication, marijuana, amphetamine, and cocaine use), demographic (food insufficiency, unemployment), and couple-related factors (having a spouse/partner who smoked, IPV involvement, being in a same-gender couple) were differentially associated with current smoking and level of intensity among men and women. Conclusions: Emergency department staff should consider the impact of polysubstance use, food insufficiency, unemployment, and whether both partners in the couple smoke when screening patients for smoking and formulating cessation treatment plans. Women in same-gender relationships and those who have experienced IPV involvement may require additional referral.